Isolation and purification of polysaccharides from Bupleurum marginatum Wall.ex DC and their anti-liver fibrosis activities - Xiao, Li; Sunniya, Hafsa; Li, Jingyi; Kakar, Mohib Ullah; Dai, Rongji; Li, Bo (Frontiers in Pharmacology, 2024)
Liver fibrosis is a pathological phenomenon in which liver tissue is replaced by fibrous and scar tissue. Without effective intervention, liver fibrosis has a high chance to develop into cirrhosis or hepatocellular carcinoma. In the field of western medicine, there is still no obvious and effective antifibrosis drugs recognized at home and abroad. Therefore, it is very urgent to develop new drugs against liver fibrosis. Bupleurum marginatum Wall.ex DC [Apiaceae] (BM)is widely grown in southwestern China, and the whole plant is used as Traditional Chinese Medicine (TCM). Polysaccharides are main natural products in lots of TCM and have been studied for their effects of reducing oxidative stress, antiinflammation and immune regulation. Herein, we investigated the extraction techniques of Bupleurum marginatum Wall.ex DC polysaccharides (BMP), the identification of their key components, and their ability to inhibit liver fibrosis in both cellular and animal models. Component identification indicated that monosaccharides in BMP mainly consisted of glucose, galactose, mannose, rhamnose, arabinose, and xylose. In vivo analysis revealed that BMP provided significant protective effects on N-Nitroso dimethylamine (NDMA)-induced liver fibrosis rats through reducing hepatomegaly, reducing tissue inflammation, and reducing collagen deposition. BMP also improved the hepatobiliary system and liver metabolism in accord to reduce the serum levels of ALT, AST, ALP, r-GT, and TBIL. In addition, BMP could reduce the level of inflammation and fibrosis through inhibition of IL-1β and TGF-β1. Cellular studies showed that the BMP could provide therapeutic effects on lipopolysaccharide (LPS)-induced cellular fibrosis model, and could reduce the level of inflammation and fibrosis by decreasing the level of TGF-β1, IL-1β, and TNF-α. Our study demonstrated that BMP may provide a new therapy strategy of liver injury and liver fibrosis.